Preparation method of high-strength, high-energy-absorption and high-impact-resistance copper-tungsten composite material
The tungsten or tungsten alloy skeleton is prepared through 3D printing technology and thermal isostatic sintering with copper powder to form a three-dimensional interpenetrating network structure, solving the problem of low reinforcement efficiency of existing copper-tungsten composite materials and achieving comprehensive performance of high strength, high absorption energy and high impact resistance.
Patent Information
- Application Number
- CN202411780927.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-04
AI Technical Summary
The existing copper-tungsten composite materials have low reinforcement efficiency and uneven stress transmission, which can easily lead to interface cracking or local damage, affecting its strength, wear resistance, impact resistance and other properties.
3D printing technology is used to prepare tungsten or tungsten alloy skeletons, combined with copper powder for thermal isostatic sintering, forming a three-dimensional interpenetrating network structure, enhancing mechanical interlock between the body and the substrate to avoid interface cracking.
The comprehensive performance of copper-tungsten composite materials with high strength, high absorption energy and high impact resistance in the range of 20 to 500℃ is achieved, which significantly improves its strength and absorption energy and extends the damage tolerance of the material.
Smart Images

Figure CN119747681A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the field of composite material preparation, in particular to a method for preparing a high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material, which is suitable for preparing a copper-tungsten composite material with three-dimensional interpenetrating properties. Background technology:
[0002] Copper-tungsten composite materials have the advantages of good mechanical properties, energy absorption, electrical contact performance and ablation resistance. They play an irreplaceable role as key materials and components in cutting-edge technology fields such as electrical appliances, machinery, electronics, semiconductors, aerospace, and national defense.
[0003] The main preparation methods of copper-tungsten composite materials are: laser shock method, laser sintering method, melt infiltration method, etc. In order to better exert the performance of the composite material, many scholars have conducted different discussions on the microstructure of the composite material. Studies have shown that the disordered grains inside the composite material will gradually reduce the grain size as the deformation continues, and eventually the lattice will be severely distorted. The interaction of crystals has an obstructive effect on the directional arrangement of crystals. Proper extension of hot pressing time is conducive to the formation of a microstructure with directional arrangement of crystals. The tortuosity of the arrangement of microscopic components in the material determines the difficulty of ions entering the electrode. The more regular the arrangement, the better the electrical properties of the material. Some scholars have found that copper materials with higher porosity have good energy absorption characteristics, which is mainly manifested in the fact that the pores are parallel to the temperature gradient direction and the good arrangement structure. The composite methods that have been developed at present often cause the reinforcement phase to be uniformly dispersed and discontinuous, thereby reducing its strengthening efficiency, and at the same time making the stress transfer uneven, which is easy to produce stress concentration, leading to cracking or local damage at the interface between the two phases, thereby affecting the strength, wear resistance, impact resistance and other properties of the copper-tungsten composite material. Summary of the invention:
[0004] The purpose of the present invention is to provide a method for preparing a high-strength, high-energy-absorbing and high-impact copper-tungsten composite material, using 3D printing technology to achieve precise design and control of the tungsten or tungsten alloy skeleton structure in the composite material, achieve high strength of the composite material, and use copper to improve the plasticity of the composite material. The tungsten or tungsten alloy skeleton and copper are no longer simply combined by the interface, but are interlaced with each other to form a mechanical interlock, which is conducive to avoiding premature failure caused by interface cracking, giving the composite material a good damage tolerance, so that the copper-tungsten composite material has excellent comprehensive properties of high strength, high energy absorption and high impact resistance in the range of 20 to 500°C.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a high-strength, high-energy-absorbing and high-impact copper-tungsten composite material, the specific steps are as follows:
[0007] Step 1: Preparation of tungsten or tungsten alloy porous material;
[0008] Using tungsten or tungsten alloy powder as raw material, laser selective melting technology is used to prepare a porous material skeleton with a three-dimensional structure, and then annealing is performed on it;
[0009] Step 2: hot isostatic pressing and sintering of tungsten or tungsten alloy porous material and copper powder to prepare copper-tungsten composite material;
[0010] The tungsten or tungsten alloy skeleton printed in step 1 is placed in a crucible together with copper powder, and the crucible is placed in a hot isostatic pressing furnace for hot isostatic pressing to obtain a copper-tungsten composite material with a three-dimensional interpenetrating network structure.
[0011] The method for preparing the high-strength, high-energy-absorbing and high-impact copper-tungsten composite material comprises the following steps: in step 1, firstly, a grid design is performed using computer-aided design software, and the designed graphic file is imported into Magics software for graphic error correction and optimization; then, the optimized graphic file is converted into an abf format file and imported into a computer control system of a laser selective melting metal forming device, and tungsten or tungsten alloy powder is used as raw material to prepare a tungsten or tungsten alloy porous material skeleton using a laser selective melting device.
[0012] In the method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material, in step 1, the three-dimensional structure of the prepared tungsten or tungsten alloy porous material skeleton includes a bionic laminate structure, a rhombic dodecahedron structure or a cubic structure.
[0013] In the method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material, in step 1, the porosity of the prepared tungsten or tungsten alloy porous material skeleton is 50-95%, and the pore size is 400μm-5000μm.
[0014] In the preparation method of the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material, in step 1, the annealing temperature is 1020-1080° C., the heat preservation is 3-10 hours, and the annealing is air-cooled to room temperature.
[0015] In the method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material, in step 1, the tungsten or tungsten alloy powder is a spherical powder with a diameter of 15 μm to 60 μm; the process parameter range of the laser selective melting technology is: the laser power is 150 to 200 W, and the scanning speed is 400 to 800 mm / s.
[0016] In the method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material, in step 2, the crucible is one of a graphite crucible, a magnesium oxide crucible, a corundum crucible, a 45 steel crucible, and a nickel crucible.
[0017] In the method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material, in step 2, the diameter of the copper powder is 100 to 300 μm.
[0018] In the preparation method of the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material, in step 2, the hot isostatic pressing heating temperature is 800-1000° C., the insulation time is 1-5 hours, the applied pressure is 100-200 MPa, and the cooling method is furnace cooling.
[0019] The preparation method of the high-strength, high-energy-absorbing and high-impact copper-tungsten composite material is that the composite material is made of tungsten or tungsten alloy porous material with a porosity of 50-95% and copper by printing with additive manufacturing technology, and the two component phases are connected to each other and interpenetrate each other in three-dimensional space; the density is 12.3-14.6g / cm 3 When the composite material is subjected to high pressure, the compressive strength reaches 678MPa and the absorbed energy reaches 196MJ / m 3 , the energy absorption is increased by more than 200% compared with tungsten or tungsten alloy skeleton.
[0020] The design idea of the present invention is:
[0021] The present invention prepares a composite material by filling copper powder into a tungsten or tungsten alloy skeleton through hot isostatic pressing. The obtained composite material has metallurgical bonding between the reinforcement and the matrix, and has high interface strength, thus showing an ideal strengthening and rigidification effect.
[0022] Tungsten or tungsten alloy has high room temperature and high temperature strength, which can give the composite material high room temperature and high temperature strength; copper has good plasticity and toughness, which can give the composite material good energy absorption and impact resistance.
[0023] The three-dimensional interpenetrating theory of the composite material design in the present invention means that after any one component in the composite material with this structure is removed, the components can maintain the integrity of the structure, and the constituent phases remain connected and interpenetrate each other in three-dimensional space. The three-dimensional interpenetrating structure is conducive to promoting stress conduction between the two phases in the composite material, reducing stress concentration, and making the deformation of the matrix and the reinforcement phase more coordinated, so that the strength of the composite material is significantly higher than the simple addition of the two-phase strength based on the law of mixture.
[0024] In the present invention, a tungsten or tungsten alloy skeleton is prepared by laser selective melting technology. This technology uses a computer-aided system to discretize the three-dimensional structure of the component into a two-dimensional data model, and adopts a stacking method that limits the raw material and the melting path of the heat source to achieve layer-by-layer stacking of the component, which is a near-net-forming preparation method. This technology can achieve rapid prototyping of tungsten or tungsten alloy skeletons, and can accurately design and control the three-dimensional network topology of the skeleton, thereby achieving effective regulation of the structure and mechanical properties of the composite material.
[0025] The advantages and beneficial effects of the present invention are:
[0026] 1. The present invention gives full play to the respective advantages of tungsten or tungsten alloy and copper, so that the composite material has high strength and rigidity, and has excellent energy absorption and impact resistance, and has a very broad application prospect.
[0027] 2. The preparation method of the composite material of the present invention fully utilizes the advantages of 3D printing technology. The three-dimensional network topological structure of the reinforcement skeleton can be accurately designed and controlled in a wide range, so the structure and mechanical properties of the composite material can be effectively regulated.
[0028] 3. The process of the present invention gives full play to the technical advantages of additive manufacturing technology, and can adjust the structural design, porosity, powder characteristics, process parameter optimization and post-heat treatment parameters to prepare a compressive strength of 678MPa and an absorption energy of 196MJ / m 3 Large-size copper-tungsten bulk composite materials.
[0029] 4. The preparation process of the present invention is simple, the cost is low, the appearance and performance of the product are fully controllable, the composite material can be prepared according to actual needs, and it is suitable for large-scale industrial production. Description of the drawings:
[0030] In the accompanying drawings of the present invention, there are provided four pictures of the compression curve comparison of two materials, a composite material sample picture, and a theoretical design model picture.
[0031] Figure 1 Printing 3D model of bionic porous skeleton designed for SolidWorks software.
[0032] Figure 2 : (a) is a photo of the prepared bionic pure tungsten porous material; (b) is a photo of the prepared bionic copper-tungsten composite material.
[0033] Figure 3 :(a) is the compression curve of bionic pure tungsten porous material; (b) is the compression curve of bionic copper-tungsten composite material. In the figure, the horizontal axis strain represents strain (%), the vertical axis stress represents stress (MPa), skeleton represents the skeleton of bionic pure tungsten porous material, and composite material represents the bionic copper-tungsten composite material.
[0034] Figure 4 :(a) is a three-dimensional model of cubic porous skeleton printing; (b) is a photo of the prepared cubic tungsten alloy porous material; (c) is a photo of the prepared cubic copper-tungsten composite material.
[0035] Figure 5:(a) is the compression curve of cubic tungsten alloy porous material; (b) is the compression curve of cubic copper-tungsten composite material. In the figure, the horizontal axis strain represents strain (%), the vertical axis stress represents stress (MPa), skeleton represents the skeleton of cubic tungsten alloy porous material, and composite material represents the cubic copper-tungsten composite material.
[0036] Figure 6 : (a) is a three-dimensional model of the printed rhombic dodecahedron porous material; (b) is a photo of the prepared rhombic dodecahedron pure tungsten porous material; (c) is a photo of the prepared rhombic dodecahedron copper-tungsten composite material.
[0037] Figure 7 :(a) is the compression curve of rhombic dodecahedron pure tungsten porous material; (b) is the compression curve of rhombic dodecahedron copper-tungsten composite material. In the figure, the horizontal axis strain represents strain (%), the vertical axis stress represents stress (MPa), skeleton represents the skeleton of rhombic dodecahedron pure tungsten porous material, and composite material represents the rhombic dodecahedron copper-tungsten composite material.
[0038] Figure 8 :(a) is the compression curve of bionic pure tungsten porous material; (b) is the compression curve of bionic copper-tungsten composite material. In the figure, the horizontal axis strain represents strain (%), the vertical axis stress represents stress (MPa), skeleton represents the skeleton of bionic pure tungsten porous material, and composite material represents the bionic copper-tungsten composite material. Specific implementation method:
[0039] In the specific implementation process, the preparation method of the composite material with light weight, high strength, high energy absorption and high impact resistance of the present invention has the following specific operation steps:
[0040] First, 3D printing technology is used, pure tungsten or tungsten alloy (WAl1) powder is used as raw material, and a porous reinforcement skeleton is prepared using AmPro SP101 laser melting equipment (produced by Suzhou Beifeng Intelligent Technology Co., Ltd.), and then copper powder is compounded with the porous reinforcement skeleton, and hot isostatic pressing is performed under vacuum or protective atmosphere, and a copper-tungsten composite material is obtained after solidification and cooling. The composite material is composed of tungsten or tungsten alloy reinforcement and copper with a volume fraction of 10% to 80% (preferably 20% to 70%), and has a three-dimensional interpenetrating network structure, which is characterized by the reinforcement and the matrix having independent topological structures and interlaced and complementary in three-dimensional space. Among them, the particle size of tungsten or tungsten alloy powder is 15-60μm (preferably 20-50μm), the porosity of tungsten or tungsten alloy reinforcement skeleton is 40%-95% (preferably 50%-70%); the diameter of copper powder is 100-300μm (preferably 150-250μm); the hot isostatic pressing heating temperature is 800-1000℃, the holding time is 1-5h, the applied pressure is 100-200MPa, and the cooling method is furnace cooling.
[0041] The present invention will be further explained below in conjunction with specific embodiments. The following embodiments are limited to illustrating the present invention but not to limiting the protection scope of the present invention.
[0042] Example 1
[0043] In this embodiment, pure tungsten powder is used as raw material, and SolidWorks software is used to design a bionic porous structure. Figure 1 As shown. The AmPro SP101 laser melting equipment was used for manufacturing, and the laser scanning speed was selected to be 500mm / s and the laser power was 180W. Figure 2 As shown in (a), the prepared biomimetic pure tungsten porous material sample has a porosity of 56% and a pore size of 500 μm. The biomimetic pure tungsten porous material encapsulated in a vacuum tube is annealed: at 1020°C, after being kept warm for 4 hours, it is cooled to room temperature at a rate of 5°C / min to obtain a biomimetic pure tungsten porous material skeleton.
[0044] The bionic pure tungsten porous material skeleton obtained by printing is placed in a corundum crucible with a diameter of 10 cm, filled with copper powder with a diameter of 160 μm, and then placed in a hot isostatic pressing furnace for hot isostatic pressing treatment. The hot isostatic pressing temperature is 920°C, the pressure is 120 MPa, and the holding time is 3 hours. Figure 2 (b) as shown.
[0045] After testing, it was found that copper and bionic pure tungsten porous material skeletons interweave with each other in three-dimensional space to form mechanical interlocking, forming a three-dimensional interpenetrating composite material.
[0046] In this example, the parameters related to the compression performance of the bionic pure tungsten porous material skeleton and the bionic copper-tungsten composite material are as follows: Under the quasi-static compression test at a compression speed of 0.5 mm / min, the compressive strength of the bionic pure tungsten porous material skeleton is 18 MPa, and the stress of the bionic copper-tungsten composite material is manifested in three regions: elastic deformation to the first peak region, followed by a continuous region, and then a densification region with rapid stress increase ( Figure 3 ); the absorption energy of the bionic pure tungsten porous material skeleton is 0.47MJ / m 3 The bionic copper-tungsten composite material absorbs 196MJ / m 3 , the absorption energy is increased by more than 200% compared with the bionic pure tungsten porous material skeleton.
[0047] Example 2
[0048] In this embodiment, tungsten alloy powder is used as raw material, and SolidWorks software is used to design a cubic porous structure. Figure 4 (a) is shown. The AmPro SP101 laser melting equipment is used for manufacturing, and the laser scanning speed is selected to be 500 mm / s and the laser power is 200 W. Figure 4 As shown in (b), the prepared cubic tungsten alloy porous material sample has a porosity of 51% and a pore size of 430μm. The cubic tungsten alloy porous material encapsulated in a vacuum tube is annealed: at 1050℃, after being kept warm for 5 hours, it is cooled to room temperature at a rate of 5℃ / min to obtain a cubic tungsten alloy porous material skeleton.
[0049] The tungsten alloy skeleton obtained by printing above was placed in a corundum crucible with a diameter of 10 cm, filled with copper powder with a diameter of 180 μm, and then placed in a hot isostatic pressing furnace for hot isostatic pressing treatment. The hot isostatic pressing temperature was 920°C, the pressure was 110 MPa, and the holding time was 4 hours. Figure 4 (c) as shown.
[0050] After testing, it was found that the copper and cubic tungsten alloy porous material skeletons interpenetrate each other in three-dimensional space to form mechanical interlocking, forming a three-dimensional interpenetrating composite material.
[0051] In this example, the compression-related performance parameters of the cubic tungsten alloy porous material skeleton and the cubic copper-tungsten composite material are as follows: Under the quasi-static compression test at a compression speed of 0.5 mm / min, the compressive strength of the cubic tungsten alloy porous material skeleton is 203 MPa, and the compressive strength of the cubic copper-tungsten composite material is 678 MPa ( Figure 5 ); the absorption energy of the cubic tungsten alloy porous material skeleton is 21MJ / m 3 The cubic copper-tungsten composite material absorbs 159MJ / m 3 , the absorption energy is increased by more than 200% compared with the cubic tungsten alloy porous material skeleton.
[0052] Example 3
[0053] In this embodiment, pure tungsten powder is used as raw material, and SolidWorks software is used to design a rhombic dodecahedron porous structure. Figure 6 (a) is shown. The AmPro SP101 laser melting equipment is used for manufacturing, and the laser scanning speed is selected to be 600 mm / s and the laser power is 180 W. Figure 6 As shown in (b), the prepared rhombic dodecahedron pure tungsten porous material sample has a porosity of 53% and a pore size of 470 μm. The rhombic dodecahedron pure tungsten porous material encapsulated in a vacuum tube is annealed: at 1050°C, after being kept warm for 3 hours, it is cooled to room temperature at a rate of 5°C / min to obtain a rhombic dodecahedron pure tungsten porous material skeleton.
[0054] The rhombic dodecahedron pure tungsten porous material skeleton obtained by printing is placed in a corundum crucible with a diameter of 10 cm, filled with copper powder with a diameter of 160 μm, and then placed in a hot isostatic pressing furnace for hot isostatic pressing treatment. The hot isostatic pressing temperature is 930°C, the pressure is 100 MPa, and the holding time is 3 hours. Figure 6 (c) as shown.
[0055] After testing, it was found that copper and rhombic dodecahedron pure tungsten porous material skeletons interweave with each other in three-dimensional space to form mechanical interlocking, forming a three-dimensional interpenetrating composite material.
[0056] In this example, the compression-related performance parameters of the rhombic dodecahedron pure tungsten porous material skeleton and the rhombic dodecahedron copper-tungsten composite material are as follows: at an impact speed of 20 m / s, the compressive strength of the rhombic dodecahedron pure tungsten porous material skeleton is 49 MPa, and the compressive strength of the rhombic dodecahedron copper-tungsten composite material is 572 MPa ( Figure 7 ); The absorption energy of the rhombic dodecahedron pure tungsten porous material skeleton is 0.63MJ / m 3 The absorption energy of the rhombic dodecahedron copper-tungsten composite material is 129MJ / m 3 , the absorption energy is increased by more than 200% compared with the rhombic dodecahedron pure tungsten porous material skeleton.
[0057] Example 4
[0058] In this embodiment, pure tungsten powder is used as raw material, the bionic porous structure is designed using SolidWorks software, and AmPro SP101 laser melting equipment is used for manufacturing, and the laser scanning speed is selected to be 600mm / s and the laser power is 150W. The prepared bionic pure tungsten porous material sample has a porosity of 59% and a pore size of 540μm. The bionic pure tungsten porous material encapsulated in a vacuum tube is annealed: at 1020°C, it is kept warm for 4 hours and then cooled to room temperature at a rate of 5°C / min to obtain a bionic pure tungsten porous material skeleton.
[0059] The bionic pure tungsten porous material skeleton obtained by printing as above was placed in a corundum crucible with a diameter of 10 cm, filled with copper powder with a diameter of 160 μm, and then placed in a hot isostatic pressing furnace for hot isostatic pressing treatment. The hot isostatic pressing temperature was 900°C, the pressure was 100 MPa, and the holding time was 3 h.
[0060] After testing, it was found that copper and bionic pure tungsten porous material skeletons interweave with each other in three-dimensional space to form mechanical interlocking, forming a three-dimensional interpenetrating composite material.
[0061] In this example, the parameters related to the compression performance of the bionic pure tungsten porous material skeleton and the bionic copper-tungsten composite material are as follows: Under the quasi-static compression test at a compression speed of 0.5 mm / min, the compressive strength of the bionic pure tungsten porous material skeleton is 16 MPa, and the stress of the bionic copper-tungsten composite material is manifested in three regions: elastic deformation to the first peak region, followed by a continuous region, and then a densification region with rapid stress increase ( Figure 8 ); the absorption energy of the bionic pure tungsten porous material skeleton is 0.35MJ / m 3 The bionic copper-tungsten composite material absorbs 178MJ / m 3 , the absorption energy is increased by more than 200% compared with the bionic pure tungsten porous material skeleton.
[0062] The results of the embodiment show that the composite material prepared by the method of the present invention has a temperature of 20-500°C and a density of 12.3-14.6 g / cm 3 When the compressive strength reaches 678MPa, the absorbed energy reaches 196MJ / m 3 The absorption energy of the tungsten and tungsten alloy skeleton is increased by more than 200%, which is significantly improved. The method of the present invention has simple process steps and low production cost, and has good application prospects in the fields of national defense, aerospace, automobile, energy, etc.
Claims
1. A method for preparing a high-strength, high-energy-absorbing and high-impact copper-tungsten composite material, characterized in that: The specific steps are as follows: Step 1: Preparation of tungsten or tungsten alloy porous material; Using tungsten or tungsten alloy powder as raw material, laser selective melting technology is used to prepare a porous material skeleton with a three-dimensional structure, and then annealing is performed on it; Step 2: hot isostatic pressing and sintering of tungsten or tungsten alloy porous material and copper powder to prepare copper-tungsten composite material; The tungsten or tungsten alloy skeleton printed in step 1 is placed in a crucible together with copper powder, and the crucible is placed in a hot isostatic pressing furnace for hot isostatic pressing to obtain a copper-tungsten composite material with a three-dimensional interpenetrating network structure.
2. The method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material according to claim 1, characterized in that: In step 1, firstly, a grid design is performed using computer-aided design software, and the designed graphic file is imported into Magics software for graphic error correction and optimization; then, the optimized graphic file is converted into an abf format file and imported into the computer control system of the laser selective melting metal forming equipment, and tungsten or tungsten alloy powder is used as raw material to prepare a tungsten or tungsten alloy porous material skeleton using the laser selective melting equipment.
3. The method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material according to claim 1 or 2, characterized in that: In step 1, the three-dimensional structure of the prepared tungsten or tungsten alloy porous material skeleton includes a bionic laminate structure, a rhombic dodecahedron structure or a cubic structure.
4. The method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material according to claim 1 or 2, characterized in that: In step 1, the porosity of the prepared tungsten or tungsten alloy porous material skeleton is 50-95%, and the pore size is 400 μm-5000 μm.
5. The method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material according to claim 1 or 2, characterized in that: In step 1, the annealing temperature is 1020-1080° C., the temperature is kept for 3-10 hours, and the annealing is then air-cooled to room temperature.
6. The method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material according to claim 1 or 2, characterized in that: In step 1, the tungsten or tungsten alloy powder is a spherical powder with a diameter of 15 μm to 60 μm; the process parameter range of the laser selective melting technology is: laser power is 150 to 200 W, and scanning speed is 400 to 800 mm / s.
7. The method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material according to claim 1, characterized in that: In step 2, the crucible is one of a graphite crucible, a magnesium oxide crucible, a corundum crucible, a 45 steel crucible, and a nickel crucible.
8. The method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material according to claim 1, characterized in that: In step 2, the diameter of the copper powder is 100 to 300 μm.
9. The method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material according to claim 1, characterized in that: In step 2, the hot isostatic pressing heating temperature is 800-1000° C., the holding time is 1-5 hours, the applied pressure is 100-200 MPa, and the cooling method is furnace cooling.
10. The method for preparing the high-strength, high-energy-absorbing and high-impact-resistant copper-tungsten composite material according to claim 1, characterized in that: The composite material is made of tungsten or tungsten alloy porous material with a porosity of 50-95% and copper printed by additive manufacturing technology. The two components are connected and interpenetrated in three-dimensional space. The density is 12.3-14.6g / cm 3 When the composite material is subjected to high pressure, the compressive strength reaches 678MPa and the absorbed energy reaches 196MJ / m 3 , the energy absorption is increased by more than 200% compared with tungsten or tungsten alloy skeleton.
Citation Information
Patent Citations
Method for preparing CuW60-CuW90 material with spherical tungsten powder
CN111922343A
Method for laser 3D printing of tungsten-copper alloy special-shaped component and component prepared through method
CN113523300A
Preparation method of structural function gradient material
CN113664217A
Preparation method of three-dimensional double-connected structure composite material based on additive manufacturing
CN114192801A
High-strength wear-resistant titanium-based bionic composite material and preparation method thereof
CN116516196A
Cited By
Pure tungsten metal, preparation method thereof and nuclear fusion device component
CN121535217A
Pure tungsten metal and method for producing same, nuclear fusion device component
CN121535217B